At twelve portraits of young women - Mann, Sally 1951- (Aperture, 2020)
"At Twelve is Sally Mann's revealing, collective portrait of twelve-year-old girls on the verge of adulthood. To be young and female in America is a time of tremendous excitement and social possibilities; it is a trying time as well, caught between childhood and adulthood, when the difference is not entirely understood. As Ann Beattie writes in her perceptive introduction, "These girls still exist in an innocent world in which a pose is only a pose -- what adults make of that pose may be the issue." The consequences of this misunderstanding can be real: destitution, abuse, unwanted pregnancy. Mann does not deny this reality, but records it, both in the faces of her subjects and in written stories that accompany thirteen of the portraits, adding another dimension to our understanding of "childhood". The young women in Mann's unflinching, large-format photographs, however, are not victims. They return the viewer's gaze with a disturbing equanimity. Poet Jonathan Williams writes, "Sally Mann's girls are the ones who do the hard looking in At Twelve--be up to it!" Partly this is a result of the remarkable rapport that Mann is able to establish with her subjects. Herself the mother of three, Mann has lived most of her life in Lexington, Virginia, where all of these pictures were taken. In fact, many of the families of the young women were cared for by her father, who was the town doctor for over forty years. So while At Twelve is an intensely personal vision of what it means, now, to be twelve and female, each of Mann's subjects is allowed the opportunity to frankly return our wondering, reminiscent gaze and to have a history of her own, rooted in a specific place at a particular moment -- at twelve." --
Same ISBN for 2024 reissue
Keywords: Mann, Sally / 1951-; Photography of children / United States; Girls / United States / Portraits; Photographie d'enfants / États-Unis; Filles / États-Unis / Portraits; Mann, Sally / 1951- / https://id.oclc.org/worldcat/entity/E39PBJjdc4RmvrqgQJhdP4w9jC; Girls; Photography of children; United States / https://id.oclc.org/worldcat/entity/E39PBJtxgQXMWqmjMjjwXRHgrq; Portraits